2011
DOI: 10.1159/000329420
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Syndrome: The GABAergic System and Circuit Dysfunction

Abstract: Fragile X syndrome (FXS) is a neurodevelopmental disorder characterized by intellectual disability, sensory hypersensitivity, and high incidences of autism spectrum disorders and epilepsy. These phenotypes are suggestive of defects in neural circuit development and imbalances in excitatory glutamatergic and inhibitory GABAergic neurotransmission. While alterations in excitatory synapse function and plasticity are well-established in Fmr1 knockout (KO) mouse models of FXS, a number of recent electrophysiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 358 publications
(207 reference statements)
5
128
0
Order By: Relevance
“…The lack of FMRP will cause down-regulation of the gammaamino butyric acid (GABA) A and B receptors and up-regulation of metabotropic glutamate receptor 5 (mGluR5) throughout the brain (22)(23)(24). FMRP is highly expressed in neurons and FMRP is critical for synaptic plasticity (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of FMRP will cause down-regulation of the gammaamino butyric acid (GABA) A and B receptors and up-regulation of metabotropic glutamate receptor 5 (mGluR5) throughout the brain (22)(23)(24). FMRP is highly expressed in neurons and FMRP is critical for synaptic plasticity (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Its lack results in an overactivity of the mGluRs, a decreased GABAergic system or delayed developmental switch in GABA polarity (D'Hulst et al, 2006;Olmos-Serrano et al, 2010;He et al, 2014), and an elevated activity of GSK-3b . Potential therapeutics, therefore, include mGluR inhibitors (Vinueza Veloz et al, 2012), GABAergic enhancers (D'Hulst andKooy, 2007;Olmos-Serrano et al, 2010;Paluszkiewicz et al, 2011;Heulens et al, 2012), and inhibitors of GSK-3b (Yuskaitis et al, 2010;Guo et al, 2012). Because intellectual ability, as well as retardation (Wang et al, 2012) involves multiple players in signal processing, bryostatin-1-like agents, for their multitargeting actions, may represent a more effective class of therapeutics than agents that target a single factor in this complex pathologic process (Vislay et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it induces alterations in the neuronal networks that are established during these critical periods 156 , possibly due to impaired gephyrin clustering and downstream signalling. Taken from a broader perspective, a major implication of the complex regulation of gephyrin clustering is that mutations and disease mechanisms interfering with the proteins and signalling cascades that regulate gephyrin clustering have the potential to perturb GABAergic transmission during critical periods of brain development 158 , and thereby to contribute to the pathophysiology of neurodevelopmental disorders 5,6,159,160 . Transcription factors, such as NPAS4, have been identified that regulate GABAergic synaptogenesis by controlling the expression of activitydependent genes, and this finding may represent a potential mechanism for such perturbations 161 …”
Section: Gephyrin and Diseases Of The Nervous Systemmentioning
confidence: 99%